2021
DOI: 10.3390/microorganisms9020222
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antimicrobial and Antiproliferative Activity of TcPaSK Peptide Derived from a Tribolium castaneum Insect Defensin

Abstract: Antimicrobial peptides (AMPs) found in the innate immune system of a wide range of organisms might prove useful to fight infections, due to the reported slower development of resistance to AMPs. Increasing the cationicity and keeping moderate hydrophobicity of the AMPs have been described to improve antimicrobial activity. We previously found a peptide derived from the Tribolium castaneum insect defensin 3, exhibiting antrimicrobial activity against several human pathogens. Here, we analyzed the effect against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…A comparative bioinformatics analysis of immunity-related transcriptomes from insects has revealed unexpected evolutionary plasticity [42]. The defensins are the dominant innate immune factors in different insect species and are generally overexpressed in many insects infected with microorganisms [10]. In this context, previous studies have been conducted to evaluate the antimicrobial activity of insect defensin and DLPs [11,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative bioinformatics analysis of immunity-related transcriptomes from insects has revealed unexpected evolutionary plasticity [42]. The defensins are the dominant innate immune factors in different insect species and are generally overexpressed in many insects infected with microorganisms [10]. In this context, previous studies have been conducted to evaluate the antimicrobial activity of insect defensin and DLPs [11,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The defensin and defensin-like AMP family have been identified in insect, plant, and mammalian. These protein species play an important role in the innate immune systems of those organisms and mainly affect Gram-positive bacteria and appear to be the abundant group throughout the inducible AMP [10]. Recently, a novel insect defensin-like peptide DLP4 is isolated and identified in immunized hemolymph and various tissues of BSF; it shares high sequence similarity (60-67.5%) to other insect defensins, such as sapecin, and lucifensin [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The same Defensin 1 is active against methicillin-resistant S. aureus strains in vitro, increases infected Caenorabditis elegans adult survivors, and shows no cytotoxicity against human erythrocytes [ 38 ]. The Defensin TcPaSK, artificial derivative of T. castaneum Defensin 3 with higher cationicity and decreased hydrophobicity, can counteract S. aureus growth through membrane permeation, but there is evidence of a possible block of cell division [ 86 ]. Oxysterlin 1, 2 and 3 from Oxysternon conspicillatum are active against MDR bacteria, such as Klebsiella pneumoniae and Pseudomonas aeruginosa , but generally not against Gram-positive bacteria with limited hemolytic activity [ 87 ].…”
Section: Proposed Applications Of Insect Ampsmentioning
confidence: 99%
“…In addition to antimicrobial nature of AMPs, studies have also reported anticancerous activities of some natural AMPs 28,29 . Recently, Fort et al have reported the dual role of defensin peptide (TcPaSK) as an antimicrobial and anti-proliferative agent 30 . In the light of earlier studies, we were also interested to assess the anticancerous activity of moricin peptide.…”
Section: Introductionmentioning
confidence: 99%